2019
DOI: 10.1021/acs.jpca.9b07734
|View full text |Cite
|
Sign up to set email alerts
|

Aufbau Principle for Diffuse Electrons of Double-Shell Metal Ammonia Complexes: The Case of M(NH3)4@12NH3, M = Li, Be+, B2+

Abstract: Positively charged or neutral metal ammonia complexes can form molecular species called solvated electron precursors (SEPs) that accommodate peripheral electrons in approximately hydrogenic diffuse orbitals. This work expands the notion of SEPs to metal ammonia complexes wherein a second coordination shell with 12 ammonia molecules is attached to M­(NH3)4 (M = Li, Be+, B2+) SEPs via hydrogen bonding. In such complexes, denoted M­(NH3)4@12NH3, the 12 outer ammonia molecules displace the peripheral electrons eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 58 publications
3
51
0
Order By: Relevance
“…In that sense these molecules are similar to the previously studied "solvated electron precursors" (SEPs), where an SEP is a complex that consists of M(L) n q+ core (M = metal, L = ligand) with one or few diffuse electrons [45][46][47][48][49][50]. Interestingly, SEPs populate atomic p-, d-, f-, and g-type orbitals in excited states.…”
supporting
confidence: 60%
“…In that sense these molecules are similar to the previously studied "solvated electron precursors" (SEPs), where an SEP is a complex that consists of M(L) n q+ core (M = metal, L = ligand) with one or few diffuse electrons [45][46][47][48][49][50]. Interestingly, SEPs populate atomic p-, d-, f-, and g-type orbitals in excited states.…”
supporting
confidence: 60%
“…For these systems, we focus on the effect of different methodologies on the optimal geometries and binding energies. Considering that CCSD­(T) provides the most accurate geometries, we recently found that MP2 geometries are very accurate for the Li­(NH 3 ) 4 , Be­(NH 3 ) 4 + , and B­(NH 3 ) 4 2+ complexes . We believe that despite the presence of a transition metal, MP2 is quite accurate for the Sc 3+ ammonia complexes as well, because of the quenched transition metal center (no 4s or 3d electron is present).…”
Section: Results and Discussionmentioning
confidence: 98%
“…Metal–ammonia coordination complexes have recently been shown to exhibit unusual electronic structure motifs. Specifically, metal complexes with saturated first coordination sphere, are best described as a positively charged M­(NH 3 ) n q + core with a number of electrons delocalized in its periphery. We have observed that both s-block and d-block metals form such species, which we named solvated electron precursors (SEPs).…”
Section: Introductionmentioning
confidence: 99%
“…In that sense these molecules are similar to the previously studied"solvated electron precursors" (SEPs), where an SEP is a complex that consists of M(L) n q+ core (M = metal, L = ligand) with one or few diffuse electrons. [42][43][44][45][46][47] Interestingly, SEPs populate atomic p-, d-, f-, and g-type orbitals in excited states. The exact Aufbau order introduced for the M(NH 3 ) 4 (M = Li, Na) SEPs is 1s, 1p, 1d, 2s, 2p.…”
Section: Introductionmentioning
confidence: 99%